Relationships among gut microbes, the interleukin family, and hypertension: a mediation Mendelian randomization study - Zhao, Shiyao; Zhang, Jing; Ding, Fuxia; Sun, Shougang (Frontiers in Nutrition, 2023)
Purpose Observational studies have increasingly recognized the influence of gut microbes on blood pressure modulation. Despite these findings, a direct causal link between gut flora and hypertension remains unestablished due to inherent confounders and the challenges of reverse causality in observational research. In this study, we sought to elucidate the causal relationship between specific gut flora and hypertension and its intermediary mediators. Methods We employed a two-sample Mendelian randomization (MR) and mediation MR analysis, analyzing 211 species of gut bacteria, with a focus on the interleukin family as potential mediators and hypertension as the primary outcome. The central methodological technique was inverse variance weighted estimation, supplemented by various other estimators. Results Our findings revealed that two bacterial species positively correlated with hypertension risk, while five had a negative association. Further validation was conducted using sensitivity analyses. Notably, our mediation MR results suggest interleukin-1 receptor type 2 (IL-1R2) as a mediator for the effect of the genus Clostridium innocuum group on hypertension, accounting for a mediation proportion of 14.07% [(Mediation effect: (b=0.0007, 95%CI: 0.0002-0.0011); Proportion mediation = 14.07% (4.26%-23.40%)]. Conclusion Our research substantiates a genetic causal relationship between specific gut microbes and hypertension, emphasizing the potential mediating role of interleukin-1 receptor type 2 (IL-1R2) and offering insights for clinical hypertension interventions.